Abdurrahman b. Kasım ve maliki mezhebindeki konumu - İbrahimoğlu, Bilal (My University, 2013)
İmam Mâlik’in Mısır’lı önde gelen talebelerinden olan Abdurrahman İbnü’l-Kâsım İmam Mâlik’in halkasında 20 yıl kalarak onun tüm ilmî birikimini elde etmiştir. Aldığı bu birikimi Mısır’da kendi ilim halkasında özellikle Kuzey Afrika ve Endülüs’ten gelen talebelere aktararak Mâlikîliğin Mısır, Kuzey Afrika ve Endülüs’e ulaşmasını ve bu coğrafyalarda kök salmasını sağlamıştır. İbnü’l-Kâsım’ın İmam Mâik’ten edindiği fıkhî meseleler, daha sonra oluşan Mâlikî eserlerinin de temelini teşkil etmiştir. Mezhebin temel başvuru kaynağı olan el-Müdevvenetü’l-Kübrâ bu eserlerin başında gelmektedir. Tüm bunların yanı sıra İbnü’l-Kâsım sergilediği fıkhî metod ile kendinden sonra gelen Mâlikî fakihlerine mezhep içi fıkhî istidlal metodunu da göstermiştir.

Abd al-Rahman ibn al Qasım, who was one of the leading Egyptian students of Imam Malik has gathered all of Imam Malik’s scholarly knowledge by studying at his private lectures for twenty years. With all the knowledge he gathered, he has started to teach his own student ring consisted of especially North African and Andulusian students; and paved the way expanding of Malikism in Egypt, North Africa and Andulusia. The matters of fiqh which ibn al-Qasm gathered from Imam Malik, was the basis of later Maliki works. Al – Mudevvenet’ul Qubra is the first among these works and serves as the foundation book for the Maliki madhab. In addition to all these, ibn al-Qasm has shown the method of fiqh evidence (istidlal) in the order (Maliki) to the later Maliki jurisprudence by performing fiqh method.
Keywords: İlahiyat; İslam Hukuku